IMPLEMENTASI PROGRAM SISTEM INFORMASI PELAYANAN UPDATE ELEMEN DATA KEPENDUDUKAN (SIPULEN) DI KECAMATAN GANEAS KABUPATEN SUMEDANG - Astri Nurmalasari (JRPA - Journal of Regional Public Administration, 2026)
The purpose of the study was to determine the Implementation of Population Data Element Update Service Information System Program (SIPULEN) in Ganeas District Sumedang Regency. The research method used in this study is a qualitative research method. The informant determination technique is purposive sampling. With informants namely the District Head, Head of the General, Personnel, and Asset Subdivision, Head of Public Service Section, Admin Operator, and the Community. The data collection technique used is literature study and field study consisting of observation, interviews, and documentation. The data validity technique used is credibility, transferability, dependability, and confirmability testing. While the data analysis technique in this study is data reduction, data display, data verification, and triangulation. Based on the results of the study, it was concluded that the Implementation of Population Data Element Update Service Information System Program (SIPULEN) in Ganeas District Sumedang Regency is running quite well. Implementation of the SIPULEN Program has weaknesses, particularly in the inconsistency of information dissemination. There are obstacles in the Implementation of the SIPULEN Program, namely the lack of information intensity and limited staff participation. Efforts to overcome these obstacles involve delivering information through various media and increasing staff participation through coaching, regular briefings, motivation, and strengthening service performance. The suggestions needed are the include establishing more consistent communication in delivering program information, conducting regular training for program implementers as advanced training, and enhancing implementer motivation through the provision of rewards, incentives, and routine coaching.